Some Effective Tight-Binding Models for Electrons in DNA Conduction: A Review - Hiroaki Yamada; Kazumoto Iguchi (Advances in Condensed Matter Physics)
Quantum transport for DNA conduction has been widely studied with interest in application as a candidate in making nanowires as well as interest in the scientific mechanism. In this paper, we review recent works concerning the electronic states and the conduction/transfer in DNA polymers. We have mainly investigated the energy-band structure and the correlation effects of localization property in the two- and three-chain systems (ladder model) with long-range correlation as a simple model for electronic property in a double strand of DNA by using the tight-bindingmodel. In addition, we investigated the localization properties of electronic states in several actual DNA sequences such as bacteriophages of Escherichia coli, human-chromosome 22, compared with those of the artificial disordered sequences with correlation. The charge-transfer properties for poly(dA)-poly(dT) and poly(dG)-poly(dC) DNA polymers are also presented in terms of localization lengths within the frameworks of the polaron models due to the coupling between the charge carriers and the lattice vibrations of the double strand of DNA.